Free help with homework

Why join Brainly?

  • ask questions about your assignment
  • get answers with explanations
  • find similar questions


2-a+b = 6, b=2
substitute b=2 in 2-a+b=6
2-a+2 = 6
4-a = 6
a = 4-6
a = -2

2 5 2
plzz click on thanks n mark it as best. hope it helps u...
Combine all similar variables in the expression.[2-a+b^(2)]=[6,2]
Reorder the polynomial 2-a+b^(2) alphabetically from left to right, starting with the highest order term.[b^(2)-a+2]=[6,2]
Remove the parentheses around the expression b^(2)-a+2.b^(2)-a+2=[6,2]
Remove the parentheses around the expression 6,2.b^(2)-a+2=6,2
Move all terms not containing a to the right-hand side of the equation.-a=-b^(2)-2+6,2
Add 6,2 to -2 to get 60.-a=-b^(2)+60
Multiply each term in the equation by -1.-a*-1=-b^(2)*-1+60*-1
Multiply -a by -1 to get a.a=-b^(2)*-1+60*-1
Simplify the right-hand side of the equation by multiplying out all the terms.a=b^(2)-60
0 0 0
The Brain
  • The Brain
  • Helper
Not sure about the answer?
Learn more with Brainly!
Having trouble with your homework?
Get free help!
  • 80% of questions are answered in under 10 minutes
  • Answers come with explanations, so that you can learn
  • Answer quality is ensured by our experts